DIVERSITY AND SOCIAL INCLUSION: : AN APPROACH IN THE ORGANIZATIONAL SCENARIO - Cristina Ribeiro Akamine, Suellen (Revista Gênero e Interdisciplinaridade, 2021)
Diversity refers to human particularities, which make individuals different from each other, and is currently considered an important and complex challenge for organizations. The company needs to understand diversity, allowing the organization to be careful in driving contextual differences, and to use it as a lever for competitive advantage, reducing possible negative impacts that may arise from this heterogeneity. This study was carried out through a literature review in Articles and other texts. The purpose of this article was to address aspects of diversity and social inclusion in the organizational scenario. The results observed through bibliographic studies were the importance of respecting diversity and inclusion aimed at the work environment, valuing the potential and talent of each individual, making it a welcoming and productive environment. It was concluded that organizations that choose policies that respect diversity, treating fairly and without discrimination, valuing the talents, ideas and different ways of thinking of each individual, enable ways to complement the knowledge within the group, making it possible to achieve success within the organization.